One‐Pot, Two‐Step Hydroxylation of the Macrocyclic Diterpenoid β‐Cembrenediol Catalyzed by P450 BM3 Mutants. Issue 24 (16th November 2016) - Le‐Huu, Priska; Petrović, Dušan; Strodel, Birgit; Urlacher, Vlada B.
Abstract: Cytochrome P450 monooxygenases (P450s) are involved in the biosynthesis of a wide range of bioactive secondary metabolites. They often introduce several oxy functionalities at different positions of a substrate through multiple steps and produce a range of oxidized derivatives. Herein, we describe a one‐pot two‐step hydroxylation of the diterpenoid β‐cembrenediol isolated from the plant Nicotiana tabacum . This 14‐membered macrocycle shows neuroprotective effects and is, along with its oxidized derivatives, of pharmaceutical interest. Sequential hydroxylations catalyzed by the regioselective P450 BM3 mutants F87A/I263L and V78A/F87G yielded the epimeric (9 S, 10 R / S )‐β‐cembrenetetraols with a diastereomeric ratio of 48:52. The replacement of the mutant V78A/F87G with L75A/V78A/F87G in the second step improves the diastereomeric ratio up to 10:90. Absolute configurations of the newly introduced hydroxy groups were determined by quantum‐mechanical calculations of NMR spectra. Abstract : Two‐step oxidation : The macrocyclic plant diterpenoid β‐cembrenediol is hydroxylated sequentially by two different regio‐ and stereoselective mutants of the cytochrome P450 monooxygenase CYP102A1 from Bacillus megaterium .